Pengembangan Modul Pembelajaran IPA Berbasis POE (Prediction, Observe, Explanation) untuk Meningkatkan Pemahaman Konsep dan Keterampilan Proses SAINS pada Siswa Kelas V - Hoirul Saleh; Irwan Koto; Bambang Parmadi (UNIB Press, 2024)
This study aims to (1) Produce POE-based science learning modules to improve students' understanding of concepts and science process skills in class V. (2) Describe the feasibility of POE-based science learning modules developed for fifth grade students. (3) Know the increase in students' conceptual understanding class V on heat and displacement material after using the POE-based science learning module. (4) Knowing the increase in science process skills of class V students after using POE-based science learning modules. This type of research is a Research and Development (R&D) development procedure that will be carried out referring to the ADDIE model research and development procedure. The research subjects were fifth grade students of SD Negeri Napallicin. Based on the results of the analysis of the feasibility assessment of the module by experts on the POE-based science learning module, linguists gave an average rating of 0.85, material experts gave an average rating of 0.88 and media experts rated it with an average of 0. 87. From the overall expert assessment, an average score of 0.87 is categorized as quite high or can be said to be valid and can be tried out with several revisions according to suggestions and input from experts. Based on the independent test table on the equal variances assumed section, it is known that the significance value is 0.023 <0.05. This indicates that the use of POE-based science learning modules has an effect on students' understanding of concepts. The significance value of the results of the science processing skills test was obtained 0.025 <0.05. This indicates that the use of POE-based science learning modules has an effect on students' science process skills.